Factors Influencing Inferiority Feelings: A Systematic Review - Amani, Dalila Zati; Taqiyah, Ilbasit; Iswinarti (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Inferiority feelings is a complex phenomenon arising from perceptions of deficiency, both real and imagined. This systematic review analyzes 14 international journals and finds that inferiority feeling is influenced by various internal, external, and demographic factors. Internal factors, such as physical disabilities, contingent self-esteem, and emotional intelligence, significantly contribute to individuals' perceptions of themselves. Meanwhile, external factors, including parenting styles and social exclusion, as well as demographic factors like parental education levels and socioeconomic conditions, also have a significant impact. These findings emphasize the need for a holistic approach in understanding and addressing inferiority feeling, which can serve as a guideline for designing effective interventions in both educational and family settings.